Pro SharePoint disaster recovery and high availability - Cummins, Stephen (Apress Imprint: Apress, 2013)
Few IT professionals take the time to learn what needs to be known to do disaster recovery well. Most labor under the pretense that good administration equals close to five-nines uptime. Most technical people do not see the value of planning for disasters until the unexpected has already happened, and the effects of a disaster involving a SharePoint farm-which today houses business information, line-of-business applications, sensitive information, extranets, and other highly important assets-can be staggering. Pro SharePoint Disaster Recovery and High Availability, Second Edition will take you through a step-by-step process to show how to build an awareness and reaction plan for the inevitable. With a focus on real-world experiences and war stories, author Stephen Cummins weaves an expert tale of woe response and offers you: Ways to see the warning signs of disaster, and ways to avoid it Ways to respond to a disaster while it is happening Perhaps most importantly, how to develop a plan to deal with disaster when it inevitably does happen